Impact of preoperative biliary drainage on postoperative outcome after pancreaticoduodenectomy: An analysis of 1500 consecutive cases. Issue 6 (26th July 2018) - De Pastena, Matteo; Marchegiani, Giovanni; Paiella, Salvatore; Malleo, Giuseppe; Ciprani, Debora; Gasparini, Clizia; Secchettin, Erica; Salvia, Roberto; Gabbrielli, Armando; Bassi, Claudio
Abstract : Background and Aim: Implications of preoperative biliary drain on morbidity and mortality after pancreatoduodenectomy are still controversial. The present study aims to assess the impact of preoperative biliary drain on postoperative outcome and to define optimal serum bilirubin cut‐off to recommend biliary drainage in patients undergoing pancreatoduodenectomy. Methods: All consecutive pancreatoduodenectomies carried out at Verona Hospital from 2005 to 2016 were retrospectively analyzed. The study population was divided into three groups: preoperative biliary drained (Stented Group), preoperative jaundice without drainage (Jaundiced Group) and the control group of non‐jaundiced, non‐stented patients (Control Group). Results: A total of 1500 patients were included. Seven hundred and fourteen patients (47.6%) received biliary drain (stented group), 258 (17.2%) patients did not (jaundiced group) and 528 (35.2%) patients represented the (control group). Major complications and mortality rates did not differ between groups. Conversely, the risk of developing surgical site infections doubled in the stented group (18.1%) (OR = 2.1, 95% CI = 1.5–2.8). In jaundiced patients, a preoperative bilirubin value greater than 7.5 mg/dL (128 μmol/L) accurately predicted the likelihood of postoperative complications. Conclusion: Preoperative biliary drain does not increase major complications and mortality rates after pancreatoduodenectomy, but it is associated with higher surgical site infection rates. In jaundiced patients, a bilirubin value greater than 7.5 mg/dL (128 μmol/L) should indicate biliary drainage.